African Fashion, Global Style : Histories, Innovations, and Ideas You Can Wear - Rovine, Victoria (Book collections on Project MUSE., 2015)
African Fashion, Global Style provides a lively look at fashion, international networks of style, material culture, and the world of African aesthetic expression. Victoria L. Rovine introduces fashion designers whose work reflects African histories and cultures both conceptually and stylistically, and demonstrates that dress styles associated with indigenous cultures may have all the hallmarks of high fashion. Taking readers into the complexities of influence and inspiration manifested through fashion, this book highlights the visually appealing, widely accessible, and highly adaptable styles.